Penguatan Literasi Konsumen dalam Ekosistem Digital: Strategi BPKN Mewujudkan Konsumen Cerdas Berkelanjutan - Arifin, Antoni Ludfi (LPPM Universitas Buana Perjuangan Karawang, 2026)
This study aims to analyze strategies for strengthening consumer literacy in the digital ecosystem and to examine the role of the National Consumer Protection Agency /Badam Perlindungan Konsumen Nasional (BPKN) in fostering a smart and sustainable consumer society. The background of this study is based on the increasing complexity of information in the digital economy, which potentially weakens consumers’ ability to make rational decisions. This research employed a qualitative approach using a literature review method, drawing on scholarly articles, academic books, and relevant policy documents. Data were collected through systematic searches in scientific databases and analyzed using thematic analysis with source triangulation to ensure validity. The findings indicate that consumer literacy, when integrated with digital education and consumer protection policies, enhances consumers’ ability to understand information, recognize their rights and obligations, and make responsible decisions. Furthermore, BPKN plays a strategic role in promoting consumer literacy through educational initiatives and policy recommendations, although challenges in policy implementation remain. This study concludes that synergy among literacy, education, and policy is essential to developing smart and sustainable consumers.